Sub-Synchronous Resonance Study for Future Scenarios in the Chilean Power System - Chavez-Orostica, H; Fuentes-Parra, C; Riquelme-Vera, E (Institute of Electrical and Electronics Engineers Inc., 2024)
Sub-Synchronous Resonance is a phenomenon that affects power systems, particularly those with series compensation. This work explores the occurrence of sub-synchronous resonance in the case of Chile that, because of its geography, counts with numerous series compensations. Three thermal generator units are analyzed using the frequency sweep method to assess the risk of sub-synchronous resonance. The results indicate a risk associated with torsional interaction and torsional amplification. © 2024 IEEE.